Application of Fused Organoid Models to Study Human Brain Development and Neural Disorders - Chen, Augustin; Guo, Zhenming; Fang, Lipao; Bian, Shan (Frontiers in Cellular Neuroscience, 2020)
Human brain organoids cultured from human pluripotent stem cells provide a promising platform for recapitulating histological features of the human brain and for neural disorder modeling. However, unlike animal models, brain organoids lack a reproducible topographic organization, which limits their application in modeling the complex biology, such as the interaction between different brain regions. To overcome these drawbacks of current technologies, brain organoids have been pre-patterned into specific brain regions and fused to form an assembloid that represents reproducible models recapitulating more complex biological processes of human brain development and neurological diseases. This approach has been applied to model interneuron migration, neuronal projections, tumor invasion, oligodendrogenesis, forebrain axis establishment, and vascularization of brain organoids. In this review, we will summarize the usage of this technology to understand the fundamental biology undergoing human brain development and disorders.